Vertical distribution of planktonic foraminifera in the southwestern Atlantic - Soranna, Maria Regina Gonçalves de Souza; Sousa, Silvia Helena de Mello e; Gaeta, Salvador Airton (Anuário do Instituto de Geociências, 2006)
Abstract